Does Fiscal Policy Benefit the Poor and Reduce Inequality in Namibia? - Namibia Statistics Agency; World Bank (World Bank, Washington, DC, 2017)
Reducing poverty and inequality continues to be an important national priority in Namibia. Vision 2030 – the country’s guiding development strategy – has a subordinate vision that points to several goals: “Poverty is reduced to the minimum, the existing pattern of income-distribution is equitable and disparity is at the minimum.” Vision 2030 is being implemented via a series of five-year National Development Plans, with the current National Development Plan IV (NDP4) covering 2012 through to 2017. NDP4 sets specific numerical targets. One is reducing the incidence of extreme poverty to less than 10 percent of individuals by the end of FY2016/17, measured at the national lower bound poverty line of N$277.54 in 2009/10. This report demonstrates that Namibia’s progressive income tax and generous social spending programs substantially reduce poverty and inequality, but the analysis also underscores the limits of what redistributive fiscal measures alone can accomplish. The economy must ultimately create more jobs for the poorest members of society to change the underlying distribution of what might be called “pre-fiscal” income; i.e., the income before households pay taxes and receive benefits from social programs. This will require structural transformation through greater investment in activities that create employment for unskilled workers and offer the potential for continuous productivity increases. This report aims to measure the effectiveness of these efforts and draws comparisons to the experiences of other countries. It estimates how major taxes and social spending programs affect individual incomes. It then assesses who benefits from or bears the burden of each instrument and by how much. This way, the analysis estimates the contribution of each instrument to reducing the poverty headcount and the Gini coefficient, a standard measure of inequality. The analysis provides evidence that can shape public debates over government spending and the design of social programs.